Symmetry-Breaking Enhanced Herzberg-Teller Effect with Brominated Polyacenes - Qian, Yuqin; Zhang, Tong; Han, Jian; Harutyunyan, Avetik R; Chen, Gugang; Rao, Yi; Chen, Hanning (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2021)
Molecular symmetry is vital to the selection rule of vibrationally resolved electronic transition, particularly when the nuclear dependence of electronic wave function is explicitly treated by including Franck-Condon (FC) factor, Franck-Condon/Herzberg-Teller (FC/HT) interference, and Herzberg-Teller (HT) coupling. Our present study investigated the light absorption spectra of highly symmetric tetracene, pentacene, and hexacene molecules of point-group , as well as their monobrominated derivatives with a lower symmetry. It was found that the symmetry-breaking monobromination allows more vibrational normal modes and their pairs to contribute to FC/HT interference and HT coupling, respectively. Through a projection of a molecule's vibrational normal modes to its irreducible representations, a linear relationship between the FC/HT intensity to the polyacene's size was deduced alongside a quadratic dependence of the HT intensity. Both theoretically derived correlations were well justified by our numerical simulations, which also demonstrated an approximately 20% improvement on the agreement with experimental line shape if the HT theory is adopted to replace the FC approximation. Moreover, for these low-symmetry monobrominated polyacenes, the FC intensity was even weaker than its FC/HT and HT counterparts at some excitation energies, making the HT theory imperative to decipher vibronic coupling, a fundamental driving force behind numerous chemical, biological, and photophysical processes.